A Series of Awake Craniotomy Procedures Performed in Iran - Mottaghi, Kamran; Nowroozpoor, Armin; Safari, Farhad; Salimi, Alireza; Nashibi, Masoud (Annals of Anesthesiology and Critical Care, 2016)
“Awake craniotomy” is a technique used in neurosurgical procedures, commonly performed to remove a tumor or an epileptogenic focus while the patient is awake. There has been an increasing trend towards performing this type of procedure because of its advantages; above all, the ability to map the eloquent cortex to reduce post-surgical neurological sequel. The aim of this article is to introduce 8 cases of awake craniotomies, performed in Loghman-e-Hakim hospital in Tehran, Iran. Patients were selected according to our specific criteria. Oral clonidine (4 g/kg), dexamethason (8 mg/IV), midazolam (0.03 mg/kg/IV), and sufentanil (3 g/kg/IV) were used as premedication. Patients underwent cerebral state monitoring and other monitoring modalities during the procedure. A laryngeal mask was used during the asleep phase of the anesthesia. General anesthesia was induced using propofol and lidocaine. Local anesthesia was provided with bupivacaine in the incision and pin insertion sites. Anesthesia was maintained using propofol and remifentanil infusion. A total of 8 patients underwent the procedure. No significant complications, including hemodynamic instability, depressed respiration, the need to put the patient to sleep before mapping or tumor resection, intraoperative seizures, aspiration, and brain edema were observed in any of our patients. In conclusion, we believe that a modified asleep-awake-awake technique instead of the asleep-awake-asleep technique may provide less complications and less need to manage the patients’ airway.“Awake craniotomy” is a technique used in neurosurgical procedures, commonly performed to remove a tumor or an epileptogenic focus while the patient is awake. There has been an increasing trend towards performing this type of procedure because of its advantages; above all, the ability to map the eloquent cortex to reduce post-surgical neurological sequel. The aim of this article is to introduce 8 cases of awake craniotomies, performed in Loghman-e-Hakim hospital in Tehran, Iran. Patients were selected according to our specific criteria. Oral clonidine (4 g/kg), dexamethason (8 mg/IV), midazolam (0.03 mg/kg/IV), and sufentanil (3 g/kg/IV) were used as premedication. Patients underwent cerebral state monitoring and other monitoring modalities during the procedure. A laryngeal mask was used during the asleep phase of the anesthesia. General anesthesia was induced using propofol and lidocaine. Local anesthesia was provided with bupivacaine in the incision and pin insertion sites. Anesthesia was maintained using propofol and remifentanil infusion. A total of 8 patients underwent the procedure. No significant complications, including hemodynamic instability, depressed respiration, the need to put the patient to sleep before mapping or tumor resection, intraoperative seizures, aspiration, and brain edema were observed in any of our patients. In conclusion, we believe that a modified asleep-awake-awake technique instead of the asleep-awake-asleep technique may provide less complications and less need to manage the patients’ airway.